All carry : a novel - Wojciechowski, Gene (New York : Crown, 2026)
"After the discovery of some old golf clubs at a garage sale, a down-on-his luck reporter discovers they suddenly make him hit perfectly. With the help of disgraced caddy, he competes at the Masters"-- Provided by publisher.
Joe is a golf reporter. He's missed more Father's Days than he cares to count because that's when he has to cover the US Open. But his son Buddy has counted every single one. Joe and Buddy's relationship is fractured at best. Then one day at a garage sale Buddy finds a woefully obsolete set of golf clubs that supposedly belonged to Jack Nicklaus and decides to give them to his father as an olive branch. When Joe takes the clubs out on a whim, he discovers something he's hitting 400 yards. No one hits the ball that far, not Tiger, not Nicklaus. Max "Hard Way" Mitchell knows golf perhaps better than anyone. He used to be one of the best caddies on the PGA Tour. But he was run out of town after sleeping with a golf pro's wife. Now he's the owner of a run-down driving range, his glory days slipping away. When Joe's golf channel has a round of layoffs and he is laid-off, and Hardway realizes that with this magical set of golf clubs Joe is better than anyone on the tour, he convinces Joe to do the seemingly impossible--win the Masters as an amateur. And to do this they'll need each other.
Keywords: Caddies -- Fiction; Fathers and sons -- Fiction; Golf -- Fiction; Golfers -- Fiction; Sports fiction; Domestic fiction; Novels; Fiction